Tax Losses and Ex-Ante Offshore Transfer of Intellectual Property - Rishi R. Sharma; Joel Slemrod; Michael Stimmelmayr (Center for Economic Studies and ifo Institute (CESifo), 2021)
We develop a positive model of multinational firm behavior and analyze a firm's incentive to transfer an intellectual property (IP) right of uncertain value offshore ex ante, i.e. before its success or failure is realized. With an asymmetric treatment of losses in the home country, the multinational firm will transfer its IP to a foreign low-tax country to avoid potentially negative profits at home. In addition, similar incentives exist to transfer the IP to a jurisdiction where tax rates are comparable or even higher than at home if the foreign jurisdiction offers a more symmetric treatment of losses.
Keywords: H25; H26; D21; F23; 330; intellectual property; corporate taxation; loss-offset; tax avoidance